0003 On the Same Wavelength? Quantifying the Associations between Eating Timing and Rest-Activity Rhythms in Free-Living Adults. (25th May 2022) - Hoopes, Elissa; D'Agata, Michele; Brookstein-Burke, Talia; Robson, Shannon; Witman, Melissa; Malone, Susan; Patterson, Freda
Abstract: Introduction: Misalignment between the central circadian clock and daily behaviors increases cardiometabolic morbidity and mortality risk, likely due to internal misalignment between central and peripheral circadian rhythms. Experimental studies suggest food intake may act as a time cue ('zeitgeber') for resetting circadian rhythms, representing a potential behavioral target to ameliorate circadian misalignment and associated health consequences. However, the extent to which eating timing relates to circadian rhythms in free-living adults is unclear. Therefore, we tested the associations between eating timing with 24-h rest-activity-rhythms (RAR), a free-living proxy for endogenous circadian rhythms, in non-shift-working adults. Methods: Adults without chronic health conditions or sleep disorders completed 14 days of 24/7 wrist accelerometry to evaluate RAR variables of interdaily stability (IS; day-to-day stability in RAR), intradaily variability (IV; within-day fragmentation of RAR), relative amplitude (RA; difference between peak vs. trough activity), L5 onset time (5-h period with lowest activity), and M10 onset time (10-h period with highest activity). Concurrently, time-stamped image-assisted diet records were obtained to generate average eating timing variables, including daily eating onset (time of first caloric intake after awakening), offset (last caloric intake time), duration (time elapsed between eating onset and offset), and caloric midpoint (time at which 50% of daily kcals were consumed), and variables illustrating irregularity in eating timing (standard deviation of eating timing variables). Pearson's correlations quantified the associations between RAR and eating timing variables. Results: Participants (N=30) were 28.0±6.6 years, 57% female, with a BMI of 23.8±2.5 kg/m2. Higher IS was correlated with lower irregularity in both eating onset (r=-0.55, p<0.01) and duration (r=-0.51, p<0.01). Higher RA correlated with earlier eating onset (r=-0.47, p<0.01), longer eating duration (r=0.53, p<0.01), and lower eating onset irregularity (r=-0.37, p<0.05). Later L5 correlated with later eating onset (r=0.67, p<0.001), offset (r=0.58, p<0.001), caloric midpoint (r=0.56, p<0.01), and greater eating offset irregularity (r=0.53, p<0.01). Later M10 correlated with later eating offset (r=0.40, p<0.05). Conclusion: Preliminary findings indicate that eating timing and RAR are moderately correlated in free-living adults. Earlier eating timing, increased eating regularity, and longer daily eating duration may represent behavioral targets for improving circadian rhythms and subsequent cardiometabolic outcomes. Support (If Any) : Support provided by the American Heart Association (#831488) and a University of Delaware Research Fund-Strategic Initiative Award.